Benefits of D-005, a lipid extract from Acrocomia crispa fruits, in the prevention of acute kidney injury induced by nephrotoxicity in rats - Sandra Rodríguez-Salgueiro; Leyanis Ocaña-Nápoles; Ambar Oyarzábal-Yera; Lucía González-Núñez; Giselle Breña-Betancourt; María Flavia Pérez-Pino; José A. Medina-Pírez; Sonia Jiménez-Despaigne; Vivian Molina-Cuevas (Brazilian Journal of Nephrology, 2021)
Abstract Introduction: Aminoglycoside-induced acute kidney injury (AKI) is a pathology closely linked to oxidative and inflammatory reactions. Taking into account the previous reported antioxidant and anti-inflammatory effects of D-005, a lipid extract obtained from Cuban palm Acrocomia crispa (Arecaceae) fruits, this work aimed to evaluate the effects of D-005 on kanamycin-induced AKI. Methods: Male Wistar rats were divided into 7 groups: negative control (vehicle, Tween 65/H2O) and six groups treated with kanamycin to induce AKI: positive control (vehicle), D-005 (25, 100, 200, and 400 mg/kg) and grape seed extract (GSE, 200 mg/kg). D-005, vehicle, and GSE oral treatments were administered once daily for seven days, 1 h before kanamycin (500 mg/kg, i.p.). Serum uric acid and urea concentrations, renal histopathology, and oxidative markers (malondialdehyde (MDA), sulfhydryl (SH) groups, and catalase (CAT) activity) were assessed. Results: D-005 significantly reduced uric acid and urea levels, starting from D-005 100 mg/kg. Histopathologically, D-005, at all the tested doses, protected renal parenchyma structures (glomeruli, proximal tubules, and interstitium). These findings were accompanied by a significant reduction of MDA and SH group concentrations as well as restoration of CAT activity. The highest percentages of inhibition were obtained with the dose of 400 mg/kg. GSE, the reference substance, also prevented kanamycin-induced biochemical and histopathological changes, as well as reduced MDA and SH groups and restored CAT activity. Conclusion: The administration of repeated oral doses of D-005 significantly protected against kanamycin-induced AKI, which could be associated with the antioxidant and anti-inflammatory effects of this extract.